Demarcating the cité française: exclusion and inclusion in colonial Algeria, 1870-1938 - Ofrath, A (2017)
This thesis discusses the unmaking of republican citizenship in colonial Algeria and the reverberations of this process in the metropole under the Third Republic, as well as demands and contestations by various populations in the colony concerning participation and rights. The attempt to establish a regime of privileges for settlers and to exclude the Muslim majority led politicians, jurists, and administrators to rely on religion and ethnicity as legal criteria to demarcate the boundaries of French citizenship. In their quest to legitimise the political exclusion of the Muslim population, politicians and legal experts from the late nineteenth century onwards portrayed Islam as an immobile and unmodern religion. Reiterated in mainland France whenever the demand for political reform in Algeria was raised, such theories gave rise to the widely-held view that being Muslim was inherently irreconcilable with being French. At the same time, the thesis examines colonial reform movements and moments of asymmetrical negotiation between populations in Algeria and the state on the demarcation of French citizenry. Both the naturalisation of the Algerian Jews and the backlash against it are re-interpreted here to highlight the pivotal role played by the local and the settler populations. In a similar vein, the thesis discusses debates sparked in the early twentieth century by Algerian Muslim campaigns for political rights, debates which yielded alternative visions of participation in the Republic. The failure of such attempts to accommodate religious difference on the eve of collapse of the Third Republic re-affirmed the colonial order in Algeria and the deep imprint it had left on conceptions of French citizenship.